2014
DOI: 10.1177/2158244014556992
|View full text |Cite
|
Sign up to set email alerts
|

Daily Self-Weighing to Control Body Weight in Adults

Abstract: The objective of this study is to review the history of daily self-weighing for weight control, discuss the possibility that self-weighing may cause adverse psychological symptoms, and propose mechanisms that explain how self-weighing facilitates weight control. A systematic forward (citation) tracking approach has been employed in this study. In the early literature, experimental tests did not demonstrate a benefit of adding daily self-weighing to traditional behavioral modification for weight loss. More rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 79 publications
3
33
0
Order By: Relevance
“…There is evidence that self‐weighing is an effective strategy for adult weight management . Although some research has investigated potential harmful correlates of weighing, those with EDs have largely been ignored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that self‐weighing is an effective strategy for adult weight management . Although some research has investigated potential harmful correlates of weighing, those with EDs have largely been ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy remains about appropriate frequency of self‐weighing in both groups. On one hand, self‐weighing is increasingly studied for weight loss, prevention of weight regain, and age‐related weight gain . However, for some, self‐weighing may be associated with negative psychological effects; one nonclinical sample of women experienced increases in anxiety and depression and a decrease in self‐esteem attributable to daily weighing …”
Section: Introductionmentioning
confidence: 99%
“…Higher frequency of self‐weighing has been shown to be associated with weight control, mainly weight loss and maintenance of weight loss . The frequency of weighing was high in the CTM group.…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 4 Regular self-weighing has been examined in literature reviews and is associated with greater 78 weight loss or prevention of weight regain (Pacanowski et al, 2014;Vanwormer, French, 79 Pereira, & Welsh, 2008; Zheng et al, 2015). A higher weighing frequency was also associated 80 with greater weight loss or less weight gain at 24-month follow-up in two large trials 81 conducted in the community ( that many of the studies reported a negative relationship between self-weighing and affect 94 (4/10), self-esteem (3/4), body evaluation (4/10) and eating behaviors or cognitions (6/13), 95 particularly for certain subgroups, such as women or young adults (Pacanowski,Linde,& 96 Neumark-Sztainer, 2015).…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…This number might increase if we could transfer the know-how of those 58 who succeeded to those who tend to regain weight. 59 After long being criticized as being responsible for the increase in disordered eating, self-60 weighing has attracted the interest of researchers as a weight-control strategy (Pacanowski, 61 Bertz, & Levitsky, 2014). Weight monitoring belongs to the strategies of weight-loss 62 maintenance identified by the National Weight Control Registry (NWCR), which has been 63 enrolling successful weight-loss maintainers for twenty years.…”
mentioning
confidence: 99%